Hydrophobic associated polymer "grafted onto" nanosilica as a multi-functional fluid loss agent for oil well cement under ultrahigh temperature. Issue 94 (26th September 2016) - Xia, Xiujian; Guo, Jintang; Feng, Yakai; Chen, Di; Yu, Yongjin; Jin, Jianzhou; Liu, Shuoqiong
Abstract : In this study, a novel hydrophobic associated polymer/nanosilica composite with a micro-crosslinking structure was synthesized to address the drawbacks of traditional polymers in ultrahigh temperature performance. Abstract : In this study, a novel hydrophobic associated polymer/nanosilica composite with a micro-crosslinking structure was synthesized to address the drawbacks of traditional polymers in ultrahigh temperature performance. The composition, micro-morphology and thermal performance of the composite were analyzed by various techniques, such as FTIR, XPS, EDS, TEM, ESEM and DSC. The results indicated that the composite possessed a strong 3-dimensional staggered space network structure, and its thermal stability was highly improved. The grafting efficiency of the modified nanosilica was high, up to 47.07% as estimated through the NaOH titration method. The applied performance of cement slurry containing the composite was also evaluated. The results showed that the composite had excellent properties, including but not limited to thermal stability, salt-tolerance, and fluid loss control. Especially, its applicable temperature was high, up to 240 °C. The mechanical properties of set cement were significantly enhanced by the inclusion of the composite, due to its pozzolanic activity and nucleation. The pozzolanic reaction of the composite was verified by the technique of solid state 29 Si MAS NMR spetroscopy, combined with XRD and SEM. MIP, BET, permeability, DLS and TOC analysis were conducted to study the working mechanism of the composite, indicating that it could obviously improve cement filter cake quality through micro-crosslinking, auto-filling action, chemisorption, increased pozzolanic reaction and accelerated cement hydration to reduce slurry filtration effectively. Consequently, the hydrophobic associated polymer grafted onto nonsilica particles enables excellent comprehensive performance of cement slurry systems and has great potential for extensive use in deep and ultra-deep oil/gas well cementing.